2017
DOI: 10.46989/001c.20879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substitution of Fish Meal with Black Soldier Fly (Hermetia illucens) Larvae Meal, in Yellow Catfish (Pelteobagrus fulvidraco) Diets

Abstract: An 8-week feeding trial was conducted to evaluate effects of replacing fish meal (FM) with black soldier fly larvae meal (BSF) on growth performance, feed utilization, and plasma parameters, for juvenile yellow catfish, Pelteobagrus fulvidraco. Six isonitrogenous and isolipidic diets were prepared substituting the FM protein with BSF protein in the following amounts: 0 (control group), 10% (BSF10), 15% (BSF15), 20% (BSF20), 25% (BSF25) and 30% (BSF30). Three replicate groups of juvenile yellow catfish (initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The survival rate was not significantly different among all groups ( when BSF larvae were included in their diets (Li et al, 2016;Hu et al, 2017;Zhou et al, 2018;Xu et al, 2020). In the current study, it was found that the protein content of C. carpio body mass (whole proximate composition) was significantly influenced by adding BSFL meals (P<0.05) (Table 3).…”
Section: Discussionmentioning
confidence: 49%
“…The survival rate was not significantly different among all groups ( when BSF larvae were included in their diets (Li et al, 2016;Hu et al, 2017;Zhou et al, 2018;Xu et al, 2020). In the current study, it was found that the protein content of C. carpio body mass (whole proximate composition) was significantly influenced by adding BSFL meals (P<0.05) (Table 3).…”
Section: Discussionmentioning
confidence: 49%
“…Significant reduction in the growth, feed intake, and protein efficiency ratio was also observed with 100% fishmeal replacement by HM in the diet of African catfish ( Clarias gariepinus ) ( Adeoye et al, 2020 ). In addition, 25% and 30% fishmeal replacement with black soldier fly larvae meal caused a significant reduction in growth performance of juvenile yellow catfish, Pelteobagrus fulvidraco ( Hu et al, 2017 ). Katya et al (2017) reported an insignificant effect on WG and SGR of juvenile barramundi, Lates calcarifer when fishmeal replacement by HM was up to 50%, but growth was impaired at a higher replacement level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, complete fishmeal replacement with BSF larvae meal does not affect the growth performance of Atlantic salmon, Nile tilapia, and Jian carp [16,32,33]. By contrast, only low dietary levels of fishmeal (20%-28%) can be replaced with BSF larvae meal without inhibiting growth in yellow catfish (Pelteobagrus fulvidraco Richardson), white shrimp (Litopenaeus vannamei Boone), and barramundi [34][35][36]. Therefore, studies on the optimal level of BSF larvae meal in different aquaculture species are necessary.…”
Section: Discussionmentioning
confidence: 99%